PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN PUPUK ORGANIK CAIR (POC) TERHADAP PERTUMBUHAN TANAMAN PAKCOY (Brasicca rapa L.) - Siti Hadijatun Suwaldi; Agus Sugianto; Abdul Basit (AGRONISMA, 2021)
Indonesia is an agricultural country where most of the population works as farmers. Therefore most of the land in Indonesia is used for agricultural production processes. Pakcoy plants need adequate nutrition during their growth, especially Nitrogen elements which can help in the vegetative growth period of the plant. The use of organic fertilizers on plants not only provides the elements needed by plants, but can also improve soil structure. This research was to determine the effect of giving liquid organic fertilizer fermented from fish offal waste, MOL (local microorganism) banana weevil and rabbit urine on the growth of pakcoy (Brassica rapa L.) plants with different concentrations and time intervals of administration. This study used a randomized block design experimental design (RBD) experimental design composed of factorial and consists of two factors. The first factor, the POC concentration consisting of 4 levels (0 ml / l, 10 ml / l, 20 ml / l, 30 ml / l) The second factor, the time interval consisting of two levels (once every 4 days, every 8 days) . The results showed that the leaf number parameters tended to be good in the K2W2 treatment (POC concentration 20 ml / l, once every 8 days) and were significantly different from K0W1 and K0W2 but not significantly different from other treatments. In general, giving various concentrations has a significant effect on the growth of pakcoy plants. The average treatment tended to be good at a concentration of 20 ml / l but not significantly different from other treatments.